AIAA Atmospheric Flight Mechanics (AFM) Conference 2013
DOI: 10.2514/6.2013-4922
|View full text |Cite
|
Sign up to set email alerts
|

Identifiability investigation of the aerodynamic coefficients from free flight tests

Abstract: The identification of the aerodynamic coefficients, based on free flight measurements, remains a difficult task for flying vehicles like space vehicles, munitions, UAV. This is mainly due to the nonlinear structure of the mathematical model describing the behavior of the vehicle in flight, the absence of an input signal, the unknown initial conditions and the nonlinear dependence of the aerodynamic coefficients on several state variables. Under these conditions, the estimation of the model parameters must be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…The nonlinear model, based on the 6-degrees-of-freedom Newton-Euler laws of motion [19], and its representation in a quasi-LPV form [9], are shortly presented hereafter.…”
Section: Mathematical Model Of a Vehicle In Flightmentioning
confidence: 99%
See 2 more Smart Citations
“…The nonlinear model, based on the 6-degrees-of-freedom Newton-Euler laws of motion [19], and its representation in a quasi-LPV form [9], are shortly presented hereafter.…”
Section: Mathematical Model Of a Vehicle In Flightmentioning
confidence: 99%
“…where a is the speed of sound, and V is the total velocity, i.e. V = [19]. The output vector y represents the measurements obtained by available sensors and observers: embedded magnetometers, accelerometers and gyroscopes, and an on-ground trajectory radar.…”
Section: A Nonlinear Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Results obtained previously in [12] have shown that the polynomial description for the pitch damping coefficient seems to be better adapted for angles α t inferior to 10 degrees. However, for larger α t , the description of the pitch damping coefficient was adjusted and spline functions were used in order to avoid the disadvantages of the polynomial representations.…”
Section: A Description Of the Mathematical Modelmentioning
confidence: 92%
“…Determination of the aerodynamic coefficients is usually done using a combination of the following techniques: free-flight tests [5], wind tunnel balance measurements [6], Computational Fluid Dynamics (CFD), empirical and semi-empirical codes such as PRODAS (PROjectile Design/Analysis System) or DATCOM. However, these techniques are usually expensive in terms of time and cost and may lack precision for some airframe configurations or flight conditions.…”
Section: Introductionmentioning
confidence: 99%